2019
DOI: 10.1111/jcpe.13064
|View full text |Cite
|
Sign up to set email alerts
|

Biologic modelling of periodontal disease progression

Abstract: Aim To investigate the synergistic role of biologic markers from saliva, serum and plaque in modelling periodontitis disease progression. Material and Methods This longitudinal study evaluated characteristics of disease progression in 114 patients with generalized moderate to severe periodontitis. The primary outcome was detection of sites with progressing attachment loss sites over 6 months in patients who received scaling and root planing or oral hygiene only. The predictive potential of 27 biomarkers in ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…Finally, it is clear that standard nonsurgical therapy of scaling and root planing lowers the microbial burden in periodontitis and decreases inflammation as an approach to controlling the disease (44,62,64). However, while the majority of the population responds well to this treatment, a portion of the population continues to demonstrate disease, with little predictive understanding of who constitutes this "nonresponding" group (70)(71)(72)(73). In humans, it is difficult to implement a prospective periodontitis protocol, and the longitudinal dynamics of the microbiome have generally been defined by comparing disease microbiomes to those posttreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is clear that standard nonsurgical therapy of scaling and root planing lowers the microbial burden in periodontitis and decreases inflammation as an approach to controlling the disease (44,62,64). However, while the majority of the population responds well to this treatment, a portion of the population continues to demonstrate disease, with little predictive understanding of who constitutes this "nonresponding" group (70)(71)(72)(73). In humans, it is difficult to implement a prospective periodontitis protocol, and the longitudinal dynamics of the microbiome have generally been defined by comparing disease microbiomes to those posttreatment.…”
Section: Discussionmentioning
confidence: 99%
“…showed potential in predicting treatment sensitivity (sensitivity and specificity: 71%). A study by Nagarajan et al (2019) showed that the baseline levels of IL-1β and MMP-8 in saliva were higher in those with progression of periodontitis after SRP or oral hygiene only.…”
Section: F I G U R Ementioning
confidence: 99%
“…Using saliva as a diagnostic fluid for point-of-care analysis for periodontal diseases is advantageous because sample collection is easy and non-invasive, and there is access to plentiful biological fluid (Korte & Kinney, 2016). Some biomarkers in saliva have been shown to be related to the treatment response to SRP (Lee et al, 2018;Nagarajan et al, 2019;Sexton et al, 2011) and could potentially be used to estimate the treatment response to SRP.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic advancements in periodontitis continue to benefit from integration of salivary biomarker information with findings from clinical and radiographic assessments (Barnes et al, 2014; de Lima et al, 2016; Miyoshi et al, 2018; Nagarajan et al, 2015). Biomolecules found in saliva have the advantage of early noninvasive detection of host defence and inflammatory events that likely precede clinical and radiographic evidence of periodontal tissue damage (Chan et al, 2012; Glimvall et al, 2012; Nagarajan et al, 2019; Salminen et al, 2014; Taylor, 2014). Acquisition of this biological information creates an opportunity for addressing critical needs for more personalized approaches to improve periodontal health, which is the basis for P4 medicine (Flores et al, 2013; Miller et al, 2010; Sagner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%